México: Construcción de identidades - Fernández Poncela, Anna M. (Pontificia Universidad Católica del Perú. Fondo Editorial, 2000)
This text reviews some of the characteristics and the means that have shaped gender identity, as part of the traditional and popular Mexican national identity. It is a matter of reflecting briefly and generally on the subject, with special emphasis, first of all, on the idea that it is a sociocultural construction, and therefore with possibilities for change. And secondly, on how the invented and mythologized image of the national soul is intimately intertwined and linked with the stereotypes and social roles assigned to each sex. This last matter being very peculiar to the Mexican context presented here.

En este texto se pasa revista a algunas de las características y los medios que han configurado la identidad de género, como parte de la identidad nacional mexicana tradicional y popular. Se trata de reflexionar de forma breve y general sobre el tema, haciendo especial hincapié, en primer lugar, en que se trata de una construcción sociocultural, y por lo tanto con posibilidades de cambio. En segundo lugar, cómo se entrelaza y vincula de forma intima la imagen inventada y mitificada del alma nacional con los estereotipos y papeles sociales adjudicados a cada sexo. Cuestión esta última muy peculiar del contexto mexicano aquí presentado.
Mexico: Identities construction
Keywords: Antropología; https://purl.org/pe-repo/ocde/ford#5.04.03